Neurocognitive Impairment and HIV Treatment Engagement in Men Who Have Sex With Men Living With HIV Who Report Chronic Pain and Substance Use - Matthew C. Sullivan; Megan R. Wirtz; Samantha M. McKetchnie; Lauren R. Gulbicki; S. Wade Taylor; Jonathan D. Jampel; Nikhil Banerjee; Conall O’Cleirigh (AIDS Research and Treatment)
This study explored relationships between neurocognitive impairment (NCI), engagement in HIV care, and functional disability among sexual minority men aged 50 years or older living with HIV, chronic pain, and recent substance use. Sixty-three participants completed cross-sectional assessments including a neurocognitive screening measure, self-reported HIV medication adherence, past-year attendance at HIV-care appointments, and indices of pain and functional impairment. Mean participant age was 57.2 years; most identified as White (55%), followed by Black/African American (42%). On average, participants reported moderate pain; 66.7% met DSM-5 criteria for a substance use disorder. Average Montreal Cognitive Assessment (MoCA) performance reflected mild NCI. Regression analyses indicated an association between poorer MoCA performance and past-year missed HIV-care appointments (B = −0.09, t (59) = −3.10, p = 0.004). Self-reported cognitive impairment was associated with more missed HIV-care visits (B = 0.20, t (59) = 4.82, p < 0.001) and greater functional disability, whereas poorer semantic fluency was associated with fewer missed HIV-care visits (B = −0.49, t (59) = −3.99, p < 0.001). Increased brief neuropsychological assessment and linkage to tailored interventions for HIV-care engagement and substance use mitigation are warranted to support PLWH with NCI in clinical care.